2019
DOI: 10.3390/su11113226
|View full text |Cite
|
Sign up to set email alerts
|

Heterogenous Energy Consumption Behavior by Firm Size: Evidence from Korean Environmental Regulations

Abstract: We analyze the interdependencies between energy usage, energy costs, renewable energy shares, economic growth, and greenhouse gas (GHG) emissions in the Korean industrial sector by employing a time-series panel vector model. Although the topic itself about has been classic one, our research to investigate diverse dynamics between large and small-mid size businesses using micro-firm level data is the first study in literature. Since firms with different sizes are put in different policy circumstances, the aggre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 25 publications
2
2
0
Order By: Relevance
“…Furthermore, our findings confirm that labor productivity is positively significant with firm size, which indicates that these firms are running at the maximum productivity level. This finding is similar to prior studies, which also summarize the positive relationship between firm size and labor productivity [34,39,79]. These justify the significant positive impact of firm size on firm performance after controlling other variables.…”
Section: Discussion and Policy Implicationssupporting
confidence: 90%
See 2 more Smart Citations
“…Furthermore, our findings confirm that labor productivity is positively significant with firm size, which indicates that these firms are running at the maximum productivity level. This finding is similar to prior studies, which also summarize the positive relationship between firm size and labor productivity [34,39,79]. These justify the significant positive impact of firm size on firm performance after controlling other variables.…”
Section: Discussion and Policy Implicationssupporting
confidence: 90%
“…However, the regression outcome from using both OLS and FGLS methods presented by [36] shows that firm size negatively affects labor productivity in Vietnamese SMEs in 1943. A similar negative result was also found by [37], who researched a survey of 3035 active Greek manufacturing firms in the years 1995 and 1999 [38,39] also reported a negative relationship between the structure of energy sources and SME firm performance. They concluded that employing internal energy generators to mitigate electricity needs to enhance firm performance, which sometimes is not economically viable for small and medium firms.…”
Section: Firm Size and Labor Productivitysupporting
confidence: 74%
See 1 more Smart Citation
“…Alternatively, SMEs could be exempt for carbon taxation as the emission levels of individual SMEs are generally small so that a carbon tax on SMEs will not achieve much in reducing emissions while costing employment significantly. In Korea, for instance, ETS and renewable portfolio standards (RPS) do not apply to SMEs (Lee and Yu 2019). Given that many Asian countries already have policies and programs in place for SMEs, exempting or compensating them would be relatively straightforward.…”
Section: Sectoral and Firm Perspectivementioning
confidence: 99%